Katalog der in den Sammlungen der Abteilung Taxonomie der Insekten des Institutes für Pflanzenschutzforschung, Bereich Eberswalde (ehemals Deutsches Entomologisches Institut), aufbewahrten Typen - XXII (Hymenoptera: Symphyta). - Oehlke, Joachim; Wudowenz, Jutta (Contributions to Entomology = Beiträge zur Entomologie, 1984)
The series of catalogues of types in the collections of Department of Taxonomy of Insects in the Eberswalde branch of the Institute of Plant Protection Research (former DEI) is continued with a second contribution from the order of Hymenoptera which covers the Symphyta. A total of 843 species are represented by 1449 specimens of types of different categories. The largest part consists of the species described by F. W. Konow. The original quotations and those from publications, the state of preservation and sometimes the nomenclature of the alphabetically listed species are discussed. Nomenclatural Acts carpentieri Konow, 1902 (Pristiphora), Lectotype